The Minimum Wage in Historical Perspective: Progressive Reformers and the Constitutional Jurisprudence of 'Liberty of Contract - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1998)
During the Progressive period of American history the debate over the minimum wage was often between those who clung to traditional economic theory as a reason for not having a minimum wage and those who saw the efficiency-wage benefits of adopting one. Although the latter argument proved quite effective in swaying many state legislatures, it may have also been a strategic argument for circumventing the Supreme Court's particular understanding of "liberty of contract." Under this doctrine, states could not pass any legislation mandating a minimum wage unless a compelling case could be made that such a wage would definitely serve the larger public interest. This paper argues that although efficiency-wage arguments might have been appealing to liberal reformers of that time, the arguments were ultimately used as a disingenuous means by which "liberty of contract" arguments could be circumvented.
Keywords: 330